Studi Kasus Tentang Implementasi Nilai-Nilai Pancasila Pada Lembaga Pendidikan Islam Al-Azhar Tingkat SMA - Pristiwiyanto Pristiwiyanto (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
This study aims to describe the implementation of Pancasila values ??at the high school level Al-Azhar Islamic education institution. The data source of this research is a team of student teachers and students of Al-Azhar High School, Menganti-Gresik. This type of research is a case study. For taking respondents using sampling techniques. Data collection techniques using observation, interview, and documentation methods. The data analysis in this study used a qualitative descriptive analysis. The results of this study indicate that: (1) SMA Al-Azhar, Menganti-Gresik has implemented the values ??of Pancasila through school culture, namely religious character, discipline, social care, environmental care, tolerance, national spirit and democracy; (2) the role of schools in shaping the character of students is very large, because in the school culture there are values ??and beliefs as well as basic assumptions that aim at creating a learning community and supporting improvements in school quality; (3) there are several obstacles, especially the low Pancasila values ??in each student